Stakeholder perceptions of the job skills and job roles required by Industrial psychologists in South Africa - Kekana, Lerato Valencia (University of the Witwatersrand, Johannesburg, 2024)
The Fourth Industrial Revolution and recent Covid-19 pandemic have brought large changes to the way work is defined and enacted, and these transitions have placed a unique demand on Industrial/Organisational Psychologists (IOPs) to help organisations and employees manage these workplace changes. This has further emphasised the need for the clarification and reassessment of the job roles and job skills required of Industrial/Organisational psychologists (IOPs) in South Africa. This study explored and compared the perceptions held by I/O psychology students and trainers (i.e., lecturers and supervisors) with regards to the job role and job skills required of IOPs in South Africa. Based on the review of literature, an online survey was designed and distributed to a group of 60 (59.4%) I/O psychology students and 41 (40.6%) I/O psychology trainers (n = 101) who voluntarily completed the survey. The survey collected both quantitative and qualitative data and this was analysed using a combination of statistics and content analysis. Both students and trainers in the sample emphasised the psychological and facilitative roles of IOPs in the workplace, with their facilitative functions taking precedence. Both groups distinguished IOPs from human resource practitioners based primarily on daily processes. Students rated most roles as significantly more important than trainers however both groups identified organisational development, employee wellbeing and work life, change management, training, psychological assessments, motivation and rewards, and research as the most important roles that IOPs fulfil in the workplace. There was agreement from both groups that the roles of IOPs would change at least moderately in the next five years. With regards to the job skills required of IOPs, a degree of congruence was observed in the top five skills that both groups noted, which included the four key skills of critical thinking; responsibility and reliability; honesty and integrity; and communication. Students prioritised people management as their fifth top skill while trainers prioritised emotional intelligence. Both groups emphasised practical work experience as the most important skill to be adequately prepared for the workplace and also identified interpersonal, communication and social skills; emotional intelligence; problem-solving; analytical and critical thinking; boldness; and business acumen as important. The findings of the study provide greater insight and possible directions for education and training of IOPs in South Africa, although further research in a broader range of stakeholders is needed.
A research report Submitted in fulfillment of the requirements for a Master of Arts , In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: industrial/organisational psychologist; job roles; job skills; Fourth Industrial Revolution; Covid-19; South Africa; SDG-8: Decent work and economic growth